Europe and whiteness: Challenges to European identity and European citizenship in light of Brexit and the 'refugees/migrants crisis'. (November 2019) - Ammaturo, Francesca Romana
This article uses the current 'refugees/migrants crisis' and Brexit as illustrative of the numerous challenges the European Union faces today when it comes to its identity and the construction of a 'European citizenship'. By discussing the proliferation of borders on the European continent and by analysing the sociological significance of such proliferation, the article argues that Europe is experiencing an ontological and epistemological rather than an existential crisis that relates to its incapacity to acknowledge, and critically engage with, its fundamental neo-colonial and neo-liberal matrix. The article argues that the stalemate experienced by the European Union with respect to its regional and global relevance can only be overcome by bringing to the surface buried or disqualified knowledges about 'who counts as European' beyond whiteness.